Plastic flow behavior for machined surface material Ti-6Al-4V with rotary ultrasonic burnishing - Jian Zhao; Zhanqiang Liu (Journal of Materials Research and Technology, 2020)
A hybrid machining technology with rotary ultrasonic roller burnishing process has been developed. There is no material removal when the machined surface is generated by the hybrid ultrasonic burnishing as comparing with other conventional cutting processes. The kinematic mechanism for plastic flow during surface generation in hybrid rotary ultrasonic burnishing Ti-6Al-4V with cylindrical roller tool was revealed in this paper. Firstly, the machining experiments were carried out for surface generation with hybrid rotary ultrasonic burnishing Ti-6Al-4V. Then, the experimental analysis was conducted and it showed that, there was little change in dimension of the rotary ultrasonic roller burnished workpiece compared to that of milled workpiece. Finally, a 3D finite element (FE) model was proposed to simulate the surface generation in hybrid rotary ultrasonic roller burnishing process. Three machining zones including pile-up deformation area, tensile deformation area, and compressive deformation area were selected for the analysis of the material plastic flow. It was found that the surface generated by rotary ultrasonic burnishing was mainly attributed to the plastic flow of material in these three deformation zones. The FE simulation results showed good agreements with the experimental ones. The proposed research results are helpful for the analysis and diagnosis of the surface generation in ultrasonic burnishing process. Keywords: Rotary ultrasonic burnishing, Surface generation, Kinematic mechanism, Plastic flow